Asymmetric Oxygen Vacancies: the Intrinsic Redox Active Sites in Metal Oxide Catalysts - Yu, Kai; Lou, Lan‐Lan; Liu, Shuangxi; Zhou, Wuzong (Advanced science, 2020)
To identify the intrinsic active sites in oxides or oxide supported catalysts is a research frontier in the fields of heterogeneous catalysis and material science. In particular, the role of oxygen vacancies on the redox properties of oxide catalysts is still not fully understood. Herein, some relevant research dealing with M1–O–M2 or M1–□–M2 linkages as active sites in mixed oxides, in oxide supported single‐atom catalysts, and at metal/oxide interfaces of oxide supported nanometal catalysts for various reaction systems is reviewed. It is found that the catalytic activity of these oxides not only depends on the amounts of oxygen vacancies and metastable cations but also shows a significant influence from the local environment of the active sites, in particular, the symmetry of the oxygen vacancies. Based on the recent progress in the relevant fields, an “asymmetric oxygen vacancy site” is introduced, which indicates an oxygen vacancy with an asymmetric coordination of cations, making oxygen “easy come, easy go,” i.e., more reactive in redox reactions. The establishment of this new mechanism would shed light on the future investigation of the intrinsic active sites in oxide and oxide supported catalysts. Asymmetric oxygen vacancies in metal oxide catalysts act as intrinsic catalytic active sites for redox reactions by making oxygen species easy come, easy go. Some relevant work focused on the active sites with asymmetric bonding situations in doped oxides, in oxide stabilized single‐atom catalysts, and at metal/oxide interface is reviewed.